Digital Literacy and Digital Competence of Teachers on Teaching English at SMKN 4 Pekanbaru - Nofriyani Zebua; Miranti Eka Putri (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
This research aims to examine the digital literacy and digital competence of teachers on teaching English and its effect. Quantitative data is the result of the correlational study in the form of a questionnaire on teachers' digital literacy and digital competence. Data processing is done by simple regression, multiple regression test and correlation test using spss version 25. The simple regression test results concluded that the literacy and competence of digital teachers on teaching English at SMKN 4 Pekanbaru are high scores. The coefficient of determination (R Square) of digital literacy and digital competence is 90.3 % and 85.4 %. Then, the effect concluded that T calc < T table ; 1,182 <4,302 and 0,567 < 4,302. According to the basis of decision making, it was concluded that the null hypothesis is accepted. it means that digital literacy and digital competence in teaching English are not significant.